Perspectives of Circadian-Based Music Therapy for the Pathogenesis and Symptomatic Treatment of Neurodegenerative Disorders - Sharma, Arastu; Moon, Eric; Kim, Geunhoo; Kang, Sung-Ung (Frontiers in Integrative Neuroscience, 2022)
Music therapy (MT) and other rhythmic-based interventions for the treatment of neurodegeneration (ND) have been successful in improving the quality of life of affected individuals. Music therapy and rhythm-based stimuli affect patients with Alzheimer’s disease (AD) and Parkinson’s disease (PD) respectively not only through cognitive channels and subjective qualifications but also through altered brain structures and neural systems. Often implicated in the pathogenesis and resulting symptoms of these diseases is the role of aberrant circadian rhythmicity (CR), namely disrupted sleep. Recent literature suggests that proper maintenance of this timekeeping framework may be beneficial for patients with neurodegenerative disorders and serve a neuroprotective role. While music therapy can improve the quality of life for neurodegenerative patients, longitudinal studies analyzing sleep patterns of affected individuals and possible mechanisms of intervention remain sparse. Furthermore, the role of music therapy in the context of circadian rhythmicity has not been adequately explored. By analyzing the links between circadian rhythmicity, neurodegeneration, and music therapy, a more comprehensive picture emerges, suggesting that possible uses of non-pharmacological circadian-based music therapy to target mechanisms involved in the pathogenesis of Alzheimer’s disease and Parkinson’s disease may enhance clinical treatment and potentially indicate neuroprotection as a preventative measure.